HUBUNGAN BREASFEEDING SELF EFFICACY (BSE) TERHADAP KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUI DI WILAYAH KERJA PUSKESMAS REJOSARI KOTA PEKANBARU - Komaria Susanti; Lisviarose Lisviarose; Rani Nursetya Ningsih (STIKes Al-Insyirah Pekanbaru, 2022)
Breast milk is the best natural food for babies. Breast milk contains various substances that are needed in the process of growth, baby development, health and immunity. There are several factors in facilitating the production and expenditure of breast milk, namely breast care, frequency of breastfeeding, stress and disease or maternal health, consumption of cigarettes or alcohol, contraceptive pills, nutritional intake. According to Riskesdas 2018, exclusive breastfeeding coverage in Indonesia 2014 was 37.3%, 2015 was 55.7%, 2016 was 54%, in 2017 it was 61.33% and in 2018 experienced a very significant decrease of 37.7% . This study aims to determine the relationship between breastfeeding self-efficacy and exclusive breastfeeding for breastfeeding mothers in the working area of ​​the Rejosari Public Health Center, Pekanbaru City. This study used a cross-sectional design. The population in this study were breastfeeding mothers with a total sample of 50 respondents using purposive sampling technique. The instrument of this research used a questionnaire. The data analysis used is univariate and bivariate analysis. Based on the results of the study, the results of the che square test were obtained with a significance value of 0.022 where <0.05, which means that there is an influence of breastfeeding self-efficacy with the success of exclusive breastfeeding in the working area of ​​the Rejosari Public Health Center, Pekanbaru City. This proves that breastfeeding mothers who have high trust will succeed in providing exclusive breastfeeding to their babies Keywords: breasfeeding self efficacy, exslusife breastfeeding